Expression Analysis and Serodiagnostic Potential of Microneme Proteins 1 and 3 in Eimeria stiedai - Wei, Wenrui (Genes (Basel), 2020)
Eimeria stiedai is an apicomplexan protozoan parasite that invades the liver and bile duct epithelial cells in rabbits and causes severe hepatic coccidiosis, resulting in significant economic losses in the domestic rabbit industry. Hepatic coccidiosis lacks the typical clinical symptoms and there is a lack of effective premortem tools to timely diagnose this disease. Therefore, in the present study we cloned and expressed the two microneme proteins i.e., microneme protein 1 (EsMIC1) and microneme protein 3 (EsMIC3) from E. stiedai and used them as recombinant antigens to develop a serodiagnostic method for an effective diagnosis of hepatic coccidiosis. The cDNAs encoding EsMIC1 and EsMIC3 were cloned and the mRNA expression levels of these two genes at different developmental stages of E. stiedai were determined by quantitative real-time PCR analysis (qRT-PCR). The immunoreactivity of recombinant EsMIC1 (rEsMIC1) and EsMIC3 (rEsMIC3) proteins were detected by Western blotting, and indirect enzyme-linked immunosorbent assays (ELISAs) based on these two recombinant antigens were established to evaluate their serodiagnostic potential. Our results showed that the proteins encoded by the ORFs of EsMIC1 (711 bp) and EsMIC3 (891 bp) were approximately 25.89 and 32.39 kDa in predicted molecular weight, respectively. Both EsMIC1 and EsMIC3 showed the highest mRNA expression levels in the merozoites stage of E. stiedai. Western blotting analysis revealed that both recombinant proteins were recognized by E. stiedai positive sera, and the indirect ELISAs using rEsMIC1 and rEsMIC3 were developed based on their good immunoreactivity, with 100% (48/48) sensitivity and 97.9% (47/48) specificity for rEsMIC1 with 100% (48/48) sensitivity and 100% (48/48) specificity for rEsMIC3, respectively. Moreover, rEsMIC1- and rEsMIC3-based indirect ELISA were able to detect corresponding antibodies in sera at days 6, 8, and 10 post E. stiedai infection, with the highest positive diagnostic rate (62.5% (30/48) for rEsMIC1 and 66.7% (32/48) for rEsMIC3) observed at day 10 post infection. Therefore, both EsMIC1 and EsMIC3 can be used as potential serodiagnostic candidate antigens for hepatic coccidiosis caused by E. stiedai.